On the analog and radio frequency performance of Junctionless Single Metal Gate cylindrical surround gate metal-oxide–semiconductor field-effect transistors. (October 2014) - Gupta, Santosh Kumar; Baishya, Srimanta
In this paper a comprehensive study of Junctionless Single Metal cylindrical surround gate (JLSM CSG) metal-oxide–semiconductor field-effect transistor (MOSFET) characteristics have been presented and compared with a conventional CSG MOSFET of identical dimensions. The variations of different analog and radio frequency performance parameters have been studied by varying the gate length, channel diameter, and metal gate workfunction using three-dimensional numerical simulations in terms of transconductance, transconductance generation factor, early voltage, unity gain cutoff frequency, maximum frequency of oscillation, etc. The JLSM CSG MOSFETs are found to exhibit superior characteristics compared to the conventional CSG MOSFETs.